UJI FITOKIMIA DAN AKTIVITAS ANTIOKSIDAN DARI EKSTRAK ETANOL BIJI KELENGKENG (Euphoria Iongan STEUD) DENGAN METODE PERENDAMAN RADIKAL 2,2-DIPHENIL-1-PICRYLHIDRAZYL (DPPH) - Husnul Chatimah; Chairul Saleh; Eva Marliana (JURNAL KIMIA MULAWARMAN, 2012)
Kelengkeng fruit already well known for Indonesian society. Not only from the contents of the fruit, but Kelengkeng also have many other beneficial from the seed, leather, root and leaves that useful for human health. In this research, phytochemical and antioxidant activity test have been done. Antioxidant activity test was carried out with scavenging test to 2,2-diphenyl-1-picrylhidrazil (DPPH) radical. On antioxidant activity test, mix of extract and DPPH are incubated for 30 minutes at 37oC, then the absorbance measured at λ = 517 nm using spectrophotometer. The absorbance from sample, blank and negative control are converted as Antioxidant Activity Absorbance (AA%). Based on result of phytochemical etanol extract, Kelengkeng contains phenolic compounds. And based on antioxidant activity test with DPPH radical scavenging method by spectrophotometer, ethanol extract of Kelengkeng has antioxidant activity about EC50(72.23±2.55) while Vitamin C as comparison has antioxidant activity about EC50(6.07±0.36).Keywords: Kelengkeng, phytochemical, antioxidant activity and DPPH